MENGATASI PERILAKU TERLAMBAT DATANG KE SEKOLAH MELALUI LAYANAN KONSELING INDIVIDUAL PENDEKATAN BEHAVIORISTIK DENGAN TEKNIK BEHAVIOR SHAPING DI SMP NEGERI 19 SEMARANG TAHUN AJARAN 2011/2012 - Supriyanto, Agus (Indonesian Journal of Guidance and Counseling: Theory and Application, 2012)
Based a phenomenon in SMP Negeri 19 Semarang that indicates behavioral symptoms of coming late to the school by some students. The main objective of this study to determine the student behavior of late coming to school can be overcome through individual counseling behavioristic approach to behavior shaping techniques. The types of research was single subject design with A-B-A design that measures behavior repeatedly targeted by period (weekly, daily, or hourly). The research subject were three clients. The technique of data collecting was interview and observation. The data was analysed descriptively based on the reaserch focus. The result showed the student’s symptom of coming late to school was appear. In the observations that have been conducted based on frequency aspect of weekly and daily duration that the third student has a behavioral form of late arrival at school after 1 hours of class begin. All of the clients at before, during, and process counseling was declining the behavior of coming late to school based the aspect of frequency and duration so that they eventually comes to school on time. The conclusion of this study is the behavior of coming late to school can be overcome through the implementation of individual counseling Behavioristic approach to the behavior shaping techniques.